PENGARUH LATIHAN PASS-MOVE TERHADAP KEMAMPUAN ACCURACY PASSING PADA PERMAINAN SEPAK BOLA DI CLUB PORSES DESA SERITANJUNG - Nopriadi, Ahmad; Handayani, Widya; Iswana, Bayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of pass-move training on the passing accuracy of U-12 to U-15 players at the PORSES Seri Tanjung Club. The sample size was 30. The population in this study was the PORSES Seri Tanjung Club soccer players.The method used in this study was a quasi-experimental study with a Pretest-Posttest Control Group Design. The instrument in this study was the Johnson Soccer Test. Data were collected from the pretest and posttest. The treatment in this study was pass-move training, and training was given for 6 weeks, with a training frequency of 3 times a week.Based on the research results and data analysis, there was a significant effect, thus it can be concluded that pass-move training influences the passing accuracy of soccer players at the PORSES Seri Tanjung Club.